Comprehensive Virome Profiling of Apple Mosaic Disease-Affected Trees in Iran Using RT-PCR and Next-Generation Sequencing - Anahita Hamedi; Farshad Rakhshandehroo; Mohammad Reza Safarnejad; Gholamreza Salehi Jouzani; Amani Ben Slimen; Toufic Elbeaino (Viruses, 2025)
Apples (Malus domestica), one of Iran’s oldest cultivated fruit crops, hold considerable economic importance. In this study, 170 apple leaf samples representing various commercial cultivars were collected across the country. RT-PCR screening targeted five common apple-infecting viruses and two viroids: apple chlorotic leaf spot virus (ACLSV), apple stem pitting virus (ASPV), apple stem grooving virus (ASGV), apple green crinkle-associated virus (AGCaV), apple mosaic virus (ApMV), apple scar skin viroid (ASSVd), and hop stunt viroid (HSVd). To identify additional or novel agents, 40 RT-PCR-negative samples were pooled into two composite groups and analyzed using next-generation sequencing (NGS). NGS was also performed on individual samples with mixed infections to retrieve full genomes. RT-PCR confirmed the presence of ACLSV, ASPV, ASGV, AGCaV, ApMV, and HSVd. NGS further revealed three additional pathogens: citrus concave gum-associated virus (CCGaV), apple hammerhead viroid (AHVd), and apricot vein clearing-associated virus (AVCaV), which were subsequently detected across the collection by RT-PCR. AGCaV was most prevalent (47.6%), followed by ACLSV (45.8%), HSVd (27.6%), AVCaV (20.5%), ASGV (17%), AHVd (15.2%), ASPV (14.1%), CCGaV (4.7%), and ApMV (3.5%). Mixed infections occurred in 67% of samples. Phylogenetic analysis based on CP genes (ACLSV, ASGV, AGCaV) and full genomes (AVCaV, AHVd) clustered Iranian isolates together, suggesting a common origin. This is the first report in Iran of AGCaV, CCGaV, ApMV, and AVCaV in apple, and notably, the first global report of AVCaV in a non-Prunus host. The findings provide the first comprehensive assessment of the sanitary status of apple trees in Iran.